PENGARUH INFRASTRUKTUR TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA ENTIKONG KECAMATAN ENTIKONG KABUPATEN SANGGAU - Hasanah, NorBaiti (Universitas Tanjungpura, 2023)
Research Objectives: 1) to know how the Infrastructure in Entikong Village, Entikong Sub-district, Sanggau Regency, 2) To know the extent of community welfare in Entikong Village, Entikong Sub- district, Sanggau Regency, 3) To know whether there is an influence of infrastructure on community welfare in Entikong Village, Entikong Sub-district, Sanggau Regency. Using quantitative approach research method. The population is the people of Entikong Village, Entikong Sub-district, Sanggau Regency. The sample size was 99 respondents and the data collection method used a questionnaire distributed to the Entikong village community. The results showed: (1) the average score of the infrastructure improvement variable is 4.56, which shows that infrastructure improvement in Entikong Village has a very good impact on various aspects of community life (2) the average score of the infrastructure improvement variable is 4.50, which shows that infrastructure improvement in Entikong Village has a very good impact on community welfare and income. (3) There is a correlation between the influence of infrastructure on community welfare with a deviation from linearity value of 0.160 0.05, so it can be concluded that there is a significant linear relationship between variables X andY. There is a significant positive influence between the variable of infrastructure improvement (X) on community welfare (Y), because the value of t-count t-table (13.847 1.998) and n = 0.05. So there is an influence between variable X and Y, or in other words Ho is rejected and Ha is accepted.